Effect of steel fibre on local pull-out behaviour of lightwight aggregate concrete in ambient and after exposure to elevated temperatures - Quek, Ervin Jing Yi (Nanyang Technological University, 2021)
Lightweight aggregate concrete (LWAC) has become increasingly popular due to its lightweight properties and high strength. This results in cost savings due to an overall decrease in dead load on the structure reducing the total amount of concrete used for the building. However, LWAC has its weaknesses. The increase in concrete strength is typically accompanied with the decrease in its fire resistance. This comes from the fact that the increase in strength usually comes from the increased density of the material causing lower fire resistance capabilities due to lower permeability. For LWAC, it usually has a brittleness issue and inferior bond behaviour as compared to Normal Weight Concrete (NWC). Steel fibres have been known to improve the strength of concrete and residual strength to a certain extent and will be introduced to improve the bond-slip behaviour of LWAC to address the issues mentioned. The percentage of steel fibres into the concrete mixture will be varied to discuss the effects on the bond-slip behaviour. This research aims to study the effects of steel fibre on the bond-slip behaviour of LWAC after exposure to various temperatures. A total of 32 experiments will be done on 100 mm and 200 mm diameter concrete specimens with a 13 mm steel reinforcing bar embedded in it. The variable parameters will be the concrete specimens’ diameter, temperature from ambient to 600 °C , and steel fibre content. Bond stress-slip curves of the experiments will be plotted and compared against the fib model code 2010 and subsequent failure mode of the experiment will be discussed. From this research works, it is found that temperature exposure may shift the failure mode from pull-out to splitting, in addition to deterioration of bond strength. The addition of steel fibre was observed to prevent the occurrence of splitting failure, as well as to improve the peak bond stress.